Graphene oxide supported Pd-Fe nanohybrid as an efficient electrocatalyst for proton exchange membrane fuel cells. (24th July 2020) - Dhali, Sunil; Karakoti, Manoj; Pandey, Sandeep; SanthiBhushan, Boddepalli; Verma, Ravindra Kumar; Srivastava, Anurag; Bal, Rajaram; Mehta, S.P.S.; Sahoo, Nanda Gopal
Abstract: The experimental realization and computational validation for graphene oxide (GO) supported palladium (Pd)-iron (Fe) nanohybrids as a new generation electrocatalyst for proton-exchange membrane fuel cells (PEMFCs) has been reported. The experimental apprehension of the present catalyst system has been initiated with the graphene oxide, followed by the doping of Pd and Fe via thermal inter calation of palladium chloride and iron chloride with the in-situ downstream reduction to get nanohybrids of the GO-Pd-Fe. These nanohybrids are subsequently characterized by RAMAN, FT-IR, UV–Vis, XRD, SEM, EDS, TEM and HRTEM analysis. Furthermore, the first principle calculations based on Density Functional Theory (DFT) with semi-empirical Grimme DFT-D2 correction has been performed to support the experimental findings. Computational results revealed the alteration of graphene electronic nature from zero-band gaped to metallic/semi-metallic on adsorption of transition metal clusters. Moreover, the defect sites of the graphene surface are more favorable than the pristine sites for transition metal adsorption owing to the strong binding energies of the former. Electrochemical studies show that GO-Pd-Fe nanohybrids catalyst (Pd: Fe = 2:1) demonstrates excellent catalytic activity as well as the higher electrochemical surface area of (58.08 m 2 /g Pd–Fe) −1 which is higher than the commercially available Pt/C catalyst with electrochemical surface area 37.87 m 2 /(g Pt) −1 . Graphical abstract: Image 1 Highlights: GO supported Pd–Fe nanohybrid has been successfully synthesized for PEMFCs. Size of Pd and Fe nanoparticles were in the range of 2.5–3.0 nm in the GO sheets. Computational analysis has been done for the validation of the GO-Pd-Fe nanohybrid. ECSA of GO-Pd-Fe (58.08 m 2 /g) was higher than Pt/C catalyst (37.87 m 2 /g).